SHIFT project ENV 52: soil fauna and litter decomposition. The use of adapted soil biological methods to study macrofauna in Amazonian rain forests. - GARCIA, M. (1998)
A comparative study of litter quantity and quality, decomposition rates, and the abundance, biomass, and respiration of soil-inhabiting microbes, arthropods and oligochaetes has been started in a polyculture forestry plantation and in plots of nearby secondary and primary forest in 1997.